The “e-Generation”: The Technological Usage and Experiences of Medical Students from a Developing Country - Priyasdarshani Galappatthy; Wasundara S. Wathurapatha; Priyanga Ranasinghe; Maheshi D. M. S. Wijayabandara; Dinuka S. Warapitiya; Krishantha Weerasuriya (International Journal of Telemedicine and Applications)
Background. The medical community is increasingly using Portable Electronic Devices (PEDs). We evaluated usage of PEDs and medical apps among medical students from Sri Lanka. Methods. This descriptive cross-sectional study was conducted at Faculty of Medicine, University of Colombo. Medical students from 2nd to 5th year were invited for the study. A self-administered questionnaire was used to collect details of PEDs availability, accessibility, and usage, perceived advantages/barriers of PEDs, and availability, accessibility, and usage of medical apps. Results. Sample size was 505 (response rate, 61.8%). Mean age was 23.2±1.3 years and majority were females (60.4%, n=305). Majority (87.5%, n=442) of students owned a PED. Nonaffordability was the most common reason for having not owning a PED (46%). Nonaffordability and lack of knowledge were key determinants of the usage of PEDs and medical “apps.” Doubts about reliability and lack of knowledge regarding reliable electronic sources of information were other significant barriers. Conclusions. Our results show that a significant majority of students owned a PED, a higher percentage than what is reported elsewhere. Considering barriers identified, it is important for institutions to promote usage of PEDs and medical apps by providing financial support, training, and knowledge to build confidence in technology.